Ultrasound as a Tool to Assess Body Fat - Dale R. Wagner (Journal of Obesity)
Ultrasound has been used effectively to assess body fat for nearly 5 decades, yet this method is not known as well as many other body composition techniques. The purpose of this review is to explain the technical principles of the ultrasound method, explain the procedures for taking a measurement and interpreting the results, evaluate the reliability and validity of this method for measuring subcutaneous and visceral adipose tissue, highlight the advantages and limitations of ultrasound relative to other body composition methods, consider its utility to clinical populations, and introduce new body composition-specific ultrasound technology. The focus of this review is adipose, although various tissue thicknesses (e.g., muscle and bone) can be measured with ultrasound. Being a portable imaging device that is capable of making fast regional estimates of body composition, ultrasound is an attractive assessment tool in instances when other methods are limited. Furthermore, much of the research suggests that it is reliable, reproducible, and accurate. The biggest limitations appear to be a lack of standardization for the measurement technique and results that are highly dependent on operator proficiency. New ultrasound devices and accompanying software designed specifically for the purpose of body composition assessment might help to minimize these limitations.